Pharmacological Action of Aloe Vera and Linseed Oil on Experimentally Induced Hemorrhoid in Rats - Noor D. Aziz (Journal of Global Pharma Technology, 2019)
Objective:-Hemorrhoids is recognized as one of the most common medical conditions in general population. It is clinically characterized by painless rectal bleeding during defecation with or without prolapsing anal tissue. This study designed to investigate the in vivo preclinical effect of aloin from aloe vera and linseed oil on experimentally induced hemorrhoid in rats by croton oil. Materials and Methods: Twenty five albino rats (150-310 gm.) involved in this study. The animals were separated into five groups (5 animals / each).The first and second groups represent negative and positive control, the third one treated with alovera ointment (10 %), the fourth group was treated with linseed oil and the last one treated with proctoheal® cream as a standard treatment. The latter four groups was induced experimentally with hemorrhoid by applying croton oil via rectoanal region. Twenty-four hours after the induction, animals of the respective groups were treated for 5 days. On the fifth day, 1 hour after the relevant treatment, blood samples were collected by cardiac puncture technique for estimating the complete blood picture and C-reactive protein. Rectum is surgically removed (2 cm) to detect macroscopically lesions, histopathological findings and evaluate rectoanal coefficient (RAC). Results:-The cytoarchitecture of rectoanal portion of the animals treated with linseed oil was near to normal, so the response rate of linseed is higher to other treatment (aloe vera ointment). Conclusion: linseed oil has a priority for alovera extract (Aloin) as well as has a beneficial effect on edema and inflammatory signs.Keywords: Hemorrhoid, Aloe vera, Linseed oil, Rat, Croton oil.